Агроекологічне обґрунтування та прогнозування динаміки популяції комах-фітофагів у системах захисту пшениці озимої в лісостепу України - Сахненко, Володимир Вадимович (НУБіП України, 2020)
Дисертація на здобуття наукового ступеня доктора сільськогосподарських наук за спеціальністю 16.00.10 «Ентомологія». Національний університет біоресурсів і природокористування України. Київ, 2020. У дисертації обґрунтовано та удосконалено технологію захисту пшениці озимої від комплексу шкідливих видів комах-фітофагів у системах контролю шкідників із застосуванням моніторингу їх розвитку та розмноження. Оцінено поширення комплексу шкідників за нових технологій вирощування пшениці озимої, що дозволить збільшити виробництво зерна в Лісостепу України. У сучасних технологіях вирощування пшениці озимої обґрунтовано фітосанітарний моніторинг як шкідливих, так і основних корисних видів комах за етапами органогенезу рослин. Уточнено біологію досліджуваних видів комах-фітофагів і визначено особливість їх розмноження від появи сходів до фази виходу рослин у трубку й молочно-воскової стиглості пшениці озимої. Досліджено багаторічно динаміку чисельності личинок двокрилих комах-фітофагів, яка зростала у вологі роки на 12–18 % у порівнянні з посушливими, що доцільно враховувати в системах вирощування пшениці озимої із застосуванням моделей прогнозу для оптимізації спеціальних хімічних засобів їх контролю у часі та просторі. Визначено основні показники впливу на формування ентомокомплексів пшениці озимої сучасних заходів захисту посівів з урахуванням факторів агроценозу зокрема, сівозміни, систем добрив і заходів захисту рослин від насіння до основних етапів органогенезу районованих та перспективних сортів. В 2002–2019 рр. виявлено особливості 3–4-річної синхронізації масових розмножень основних популяцій шкідників пшениці озимої в регіоні досліджень. Установлено взаємозв’язки чисельності основних шкідливих видів комах з абіотичними, антропічними та іншими чинниками при вирощуванні пшениці озимої за загальноприйнятими технологіями. Розроблено нові підходи щодо комплексної оцінки особливостей популяційних циклів та ефективності захисних заходів від основних шкідників пшениці озимої в Лісостепу України. Встановлено ефективність сучасних організаційно-господарських та хімічних захисних заходів проти комплексу шкідливих видів комах-фітофагів на основі розроблених моделей прогнозу розмноження комплексу шкідників пшениці озимої. Обґрунтовано технологію внесення бакових сумішей із додаванням до діючих речовин інсектицидів – імідаклоприд, диметоат, хлорпірифос або тіаметоксам і рідкого азотного добрива КАС, 32 %, 1 % при протруєнні і 7–10 % при обприскуванні. Це підвищило ефективність захисної дії інсектицидів на 27,3–35,8 % у порівнянні з іншими варіантами та в середньому на 86,5 % дозволяє контролювати шкідливі види досліджуваних ентомокомплексів.
Dissertation for obtaining the scientific degree of doctor of agricultural sciences after specialty 16.00.10 «Entomology». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2020. The thesis substantiates the improved technology of protecting winter wheat from the complex of harmful phytophagous insect species in protection systems using development and reproduction monitoring, as well as the distribution of phytophagous complex in new field crop rotations when growing winter wheat, which will increase production in the forest-steppe of Ukraine. The analysis of the long-term dynamics of the number of pests of winter wheat in the conditions of the Forest-Steppe of Ukraine demonstrates the modern features of the formation of phytophagous groups by the stages of organogenesis of cultivated plants and the formation of crop yields. In 2002–2018 in the Forest-Steppe of Ukraine, insect species were found and the structure of the entomocomplex was clarified: soil, leaf-eating, internal sturgeon, sucking harmful insect species, contributed to a decrease in winter wheat productivity by 25–37 %, density of productive stalk growth by 8–14 %, the spread of insect pathogens to 24 % of the surveyed areas, as well as a decrease in winter hardiness and grain quality by 21 and 36 %, respectively. Analysis of the species composition of pests indicates that, in a systematic sense, the majority of harmful species belong to a number of Coleopterа and Diptera and Lepidoptera – 42.72 %, 14.56 and 17.48 %, respectively, of the total number of identified phytophagous insects. The representatives of the order of Hemiptera – 12–62 %, Diptera – 4.85 %, Hemynoptera – 3.88 % and Thysanoptera – 1.94 % were relatively low. The study of patterns in the dynamics of the abundance of a complex of harmful insect species and the determination of the causes of their mass reproduction and distribution was of particular importance for the farms of the research region. In the new agro-biocenoses, which turned out to be modern land with highly efficient use of mixtures of special chemical measures to control the mass distribution of both ground and intra-stem pests of winter wheat. It is important to develop a multi-year forecast of the dynamics of their populations, developed on the basis of predictors of many-year weather fluctuations and measures of modern technologies of cultivation of field crops. A significant increase in the number of Swedish and black wheat flies and a complex of other insects – phytophages – as the main pests of winter wheat at the main stages of grain yield formation has been established. During the years of research, generally accepted and new technologies of farming systems were applied in the basic farms of the observation zone. At the same time, the dynamics of internal pest pests increased in 2002–2005 and decreased in 2006–2019. In particular, in 2011–2015, the amount of damage to plants by the larvae of these insects was 7–10 % less than in previous periods of observation, indicating the importance of taking abiotic and other factors into account when applying control measures to these phytophages. However, when organic farming is introduced into production, including the use of mainly the self-regulation mechanisms of the entomocomplex, the number of intraocular pests increases by a factor of 2 or more compared with other observation options. It is characteristic that the relatively arid conditions of 2016–2019. They turned out to be negative for the reproduction and survival of intrastate pests using the generally accepted and newest technologies of growing winter wheat. During the years of research, the bugs turned out to be relatively numerous, especially Eliya, a sharp-headed and harmful turtle. In the grains damaged by them, the quality of gluten deteriorated, which negatively affected the baking properties of flour. Given the prediction of pest breeding, to protect winter wheat from these phytophages (especially on crops with high agrofone), it is necessary to take both organizational and economic measures (a set of agrotechnical techniques), and use modern mixtures of high-quality chemical plant protection products. It is worth noting that the use of modern disinfectants - insecticides in 2010–2019 contributed to the reduction in the number of grain ground beetles to 0,3 m2. At the same time, there was a mass migration of numbers for winter wheat crops, and the survival of this species was observed mainly after stubble precursors; it is important to take into account when applying the new protection systems for winter wheat with models of the population dynamics of the complex of phytophages. The population of the winter noctuid was also formed cyclically with fluctuations in abundance, which was due to the intra-population mechanisms of modern entomocomplex. Reduction in the number of caterpillars of wheat shovel in 2013–2019 It depended both on fluctuations in weather and climatic conditions, and special measures to protect winter wheat shoots from pests in field crop rotations when eggs are laid by females and at the beginning of the development of caterpillars of the first age. It was established that in 2002, 2003, 2006, 2010, 2014 the number of heat fly larvae also increased 2.3–4.5 times compared with other years of observation. The use of new forms of insecticides for seed dressing contributed to the control of abundance at the species and population levels with a decrease in the number of larvae to 1,3 m2 compared to control. Conducted studies indicate the high efficiency of insecticide intoxication of the stairs and the importance of this event for managing the seasonal dynamics of the number of internal phytophages in the Forest-Steppe of Ukraine. Thus, the damage of wheat by winter larvae of wheat fly when using insecticides for seed dressing was significantly highly effective in 2008–2013 and in 2015–2019 compared to the number in 2002–2006. In resource-saving technologies of growing wheat in winter, reasonable remote high-performance technologies of phytosanitary monitoring of both harmful and useful insect species according to the stages of plant organogenesis. It has been established that the relatively high number of the complex of harmful and useful insect species is accompanied by the phases of the release of plants into the tube and the milky-wax ripeness of winter wheat. At the same time, the long-term dynamics of the number of larvae of Diptera phytophagous insects grows in humid years by 12–18 % compared to arid, which should be taken into account in the systems for growing winter wheat with the use of special chemical and biological means of controlling the complex of phytophagous insects. In the production of grain in the Forest-Steppe of Ukraine, growing technologies turned out to be relevant, which influenced the effectiveness of crop protection methods from the pest complex. Thus, according to the principle of effective localization, it is worthwhile to reduce the production of marketable wheat grain on soils with relatively low humus indices in favor of forage crops, as a result, will increase the number of predatory ground beetles and other species of beneficial insects in agrocenoses. When planning and developing crop rotations, it is advisable to pay attention to biological protection measures in order to reduce the number of winter and other types of burrowing shovels. In the Forest-Steppe of Ukraine, modern systems for the protection of grain crops include the use of integrated protection starting from optimization of crop rotation, preparing seeds for sowing and controlling the structure of the entomocomplex at the initial phases of plant development, in particular, increasing the resistance of plants against the complex of phytophages and other harmful factors by dressing seeds with insecticides while processing of its micro-and macro. In modern field crop rotations in the system of protection of both winter wheat and the previous crop, the amount of applied insecticides ranges from 0.1–0.8 l/ha. At the same time, to obtain the main grain products of both winter wheat and leguminous crops, the amount of insecticides applied is 2–4 times higher than their use on the crops of their predecessors. In the new technologies of protecting winter wheat from pests, the use of liquid nitrogen fertilizer UAN is of particular importance, 32 % of which, when applied in mixtures with insecticides, increases their efficiency by 30–35 % compared to ammonium nitrate and urea. It is characteristic that when applying this fertilizer with seed dressing preparations (1 %), and also as the main feed 100–180 l/ha and for foliar nutrition 12–18 l/ha, the loss of beneficial types of arthropods was not observed, and the effectiveness of insecticides against harmful species of insects significantly increased compared with other tank mixtures of substances. At the same time, marginal spraying of wheat shoots with a winter insecticide with the content of the active ingredient imidocloprid, 0.15 l/ha with a urea-ammonia mixture (CAM, 32 %), and reliably reducing the number of adult pests. Continuous spraying of crops with insecticides with etc. dimevit (1 l/ha) with CAS solution, 32 %, 10 l/ha was also found to reduce the number of larvae of swedish, black wheat flies and other phytophagous insects compared to the control. The high efficiency of modern protective measures against the complex of harmful species of insect phytophages on the variants with the use of prediction models for the reproduction of the complex of winter wheat pests has been noted. In particular, tank mixtures with the use of active substances flutriafol and Tiabendazole, carbendazimiv with the addition of active substances – imidacloprid or dimetoate or chlorpyrifos and cypermethrin, or lambda-cyhalothrin. This helps to reduce the number of the complex of harmful insect species and does not exert a negative impact on beneficial species of organisms, and also increases the effectiveness of the protective action by 27.3–35.8 % of modern preparations and allows controlling up to 86.5 % of harmful insect species in the structures of the agrocenosis compared with conventional technologies.
Keywords: пшениця озима; комахи-фітофаги; структура ентомокомплексу; багаторічний прогноз; моніторинг; фенологія; сорти; добрива; діючі речовини; інсектициди; winter wheat; pests; entomocomplex structure; long-term forecast; monitoring; phenology; fertilizers; insecticides